2022
DOI: 10.1038/s41467-022-30259-x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing erosion of X-chromosome inactivation in human embryonic stem cells

Abstract: X-chromosome inactivation is a paradigm of epigenetic transcriptional regulation. Female human embryonic stem cells (hESCs) often undergo erosion of X-inactivation upon prolonged culture. Here, we investigate the sources of X-inactivation instability by deriving new primed pluripotent hESC lines. We find that culture media composition dramatically influenced the expression of XIST lncRNA, a key regulator of X-inactivation. hESCs cultured in a defined xenofree medium stably maintained XIST RNA expression and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 116 publications
0
19
0
Order By: Relevance
“…X-linked genes play a vital role in different biological pathways, including early development, cell fate specification and pluripotency exit (Cloutier et al, 2022; Marahrens et al, 1997; Schulz et al, 2014; Zhang et al, 2016). However, X-linked genes in male and female cells are expressed monoallelically.…”
Section: Discussionmentioning
confidence: 99%
“…X-linked genes play a vital role in different biological pathways, including early development, cell fate specification and pluripotency exit (Cloutier et al, 2022; Marahrens et al, 1997; Schulz et al, 2014; Zhang et al, 2016). However, X-linked genes in male and female cells are expressed monoallelically.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the X‐chromosome inactivation state in human EPSCs has not been scrutinized (Yang, Liu, et al, 2017). More recently, Cloutier et al (2022) pinpointed the evolutional difference in X‐chromosome inactivation in vivo between mice and humans (Cloutier et al, 2022). They showed that the X‐chromosome inactivation in vitro can be controlled by lithium ion.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been shown that DNA methylation of the XIST promoter on Xi is involved in Xi erosion (Fukuda et al , 2021), the detailed mechanism underlying Xi erosion remains unclear. Notably, however, a recent study has shown that lithium chloride (LiCl), a component of conventional hPSC culture media such as mTeSR1, activates WNT signaling and induces Xi erosion, and the removal of LiCl from the medium prevents hPSCs from Xi erosion (Cloutier et al , 2022). LiCl also induces Xi erosion in mouse epiblast stem cells (EpiSCs; Cloutier et al , 2022).…”
Section: Discussionmentioning
confidence: 99%